Holding on to Objects in Motion: Two Māori Musical Instruments in the Peabody Essex Museum - Mackintosh, Lucy (Material Culture Review, 2012)
Two Māori flutes in the Peabody Essex Museum provide a multi-faceted view of objects in motion. The flutes, carved in New Zealand, were collected by a Salem captain during a trading voyage and donated to the museum in 1807. This paper follows the movements of the flutes across space and time, tracing the circuits of Māori cosmogony, Western trade, cross-cultural exchange, and breath and sound embodied in the flutes. The paper suggests that these small, carefully crafted instruments, requiring close engagement and focus in order to “play,” have their own logic of circulation and organizing power and move across temporal and spatial boundaries, categories and musical planes, refusing to become static, lifeless museum objects.